(untitled) (The Research of Medical Science Review, 2025)
Background: Diabetes mellitus requires lifelong management, with medication adherence being crucial for preventing complications like cardiovascular disease and neuropathy. In Peshawar, diabetes is a growing public health concern, and Lady Reading Hospital plays a key role in managing diabetic patients. However, adherence levels and influencing factors remain understudied. This study assesses drug adherence among diabetic patients at Lady Reading Hospital, identifying barriers to improve patient outcomes and inform healthcare strategies for better diabetes management in the region. Objective: This study aims to assess the level of drug adherence among diabetic patients at Lady Reading Hospital, Peshawar, and identify factors influencing their adherence. The findings will help improve diabetes management by addressing adherence gaps and guiding healthcare strategies to enhance patient outcomes. Methodology: A quantitative, descriptive cross-sectional study design was employed to assess drug adherence among diabetic patients at Lady Reading Hospital, Peshawar. A convenient sample of 110 diabetic patients attending the outpatient department (OPD) and diabetes clinics was selected for the study. Self-administered questionnaires based on the Morisky Medication Adherence Scale (MMAS-8) were used to gather data, along with clinical and demographic data. To assess adherence levels and pinpoint the causes of non-adherence, statistical analysis was done. Results: The survey of 110 diabetic patients at Lady Reading Hospital revealed that the majority were middle-aged, unemployed, and had low educational levels. Type 2 diabetes was the most common form of the condition. While 64.3% consistently took their medication, 44.4% reported skipping doses, mainly due to forgetfulness (35.7%) or cost (8.7%). Many patients struggled with understanding their medications and accessing them. Despite receiving reminders (mainly from family members), 32.5% rated their diabetes management as poor. These findings highlight the need for improved patient education, better access to medications, and stronger communication with healthcare providers. Conclusion: The study highlights the serious problem of diabetic patients at Lady Reading Hospital not taking their medications as prescribed, which can have a major influence on how their condition is managed and result in problems. Even though some patients took their drugs as directed, many reported missing doses because of things like financial hardships and forgetfulness. The results point to a lack of knowledge and difficulties in obtaining prescription drugs. These problems highlight the necessity of focused interventions, such as ongoing patient education, enhanced counseling, and methods to overcome obstacles like cost and accessibility. Improving adherence will ultimately result in better diabetes control and a lower risk of complications, thus it will be crucial to improve communication between patients and healthcare professionals. Further research is necessary to identify the key factors contributing to poor adherence and to develop tailored strategies that can enhance patient outcomes and reduce the burden of diabetes in this region.